Shingles: Prevention and treatment - Dilshaad Asmal (South African Family Practice)
Varicella, a childhood disease, is caused by the varicella-zoster virus (VZV). Primary infection occurs when the virus comes into contact with the mucosa of the respiratory tract or conjunctiva. At these sites, viral multiplication occurs with subsequent haematogenous spread. VZV persists predominantly in the sensory ganglia of the cranial and spinal nerves. Shingles is the result of a reactivation of this residual latent virus. A number of triggers may cause a reactivation of this infection and this manifests as a painful vesicular eruption in a dermatomal distribution.